2016
DOI: 10.1002/maco.201608837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alloy composition on the oxidation‐induced boron depletion in cast Ni‐base superalloy components

Abstract: Cover: High temperature corrosion attack of the surface of a heat resistant high-alloy steel for boiler tubes (DMV304HCu) after exposure to a chlorine-free coal-power-plant ash at 625 °C for 1000 hours (cross section/false colors): Coal-power-plant ash containing sulphur, sodium, potassium, calcium and iron-rich oxides (dark red and violet); outer iron-rich oxide scale (yellow); inward growing chromia scale containing sulphur (turquoise); small chromium sulphides at the corrosion front in the metal subsurface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…For ground specimen no boron peak is found. A similar effect of hampering boron diffusion through alumina scale was observed by Nowak et al [16].…”
Section: Oxidation Modelingsupporting
confidence: 79%
“…For ground specimen no boron peak is found. A similar effect of hampering boron diffusion through alumina scale was observed by Nowak et al [16].…”
Section: Oxidation Modelingsupporting
confidence: 79%
“…In order to conrm the presence of both Py and APBA units in the p(APBA-co-Py) chains, its FESEM-WDX analysis 62,63 was performed together with those of homopolymers (Fig. 6).…”
Section: Fesem-wdx Analysismentioning
confidence: 99%
“…Indeed, Binder et al [8] evidenced that increas ing the boron concentration in Cr Ni Co Fe alloys accelerated the devel opment of complex spinels at the expense of the more protective oxide Cr 2 0 3 • Similarly, Barrett et al [9] concluded for nickel basecl superal loys that boron favored the formation of NiO oxide at the expense of the more protective Al 2 0 3 and aluminate spinel oxides. Moreover, sev eral studies evidenced boron oxides in the oxide scale of nickel based alloys: CrB0 3 [10,11], Al 3 B0 6 [10], A1 4 Bi0 9 [12] and Ni 2 Cr0 2 (B0 3 ) [11]. Boron is incorporated in the oxide scale for two main reasons: the high thermodynamic stability of the boron oxides and the high diffusiv ity of boron in nickel [11] (the boron cliffusivity in nickel is between 3 and 4 orders of magnitude higher than that of Ni, Cr or Al [10)).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sev eral studies evidenced boron oxides in the oxide scale of nickel based alloys: CrB0 3 [10,11], Al 3 B0 6 [10], A1 4 Bi0 9 [12] and Ni 2 Cr0 2 (B0 3 ) [11]. Boron is incorporated in the oxide scale for two main reasons: the high thermodynamic stability of the boron oxides and the high diffusiv ity of boron in nickel [11] (the boron cliffusivity in nickel is between 3 and 4 orders of magnitude higher than that of Ni, Cr or Al [10)). Then, the diffusion of boron towards the oxide scale can largely deplete the bulk alloy from boron, thus degrading the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation